2020
DOI: 10.1093/mnras/staa597
|View full text |Cite
|
Sign up to set email alerts
|

H i asymmetries in LVHIS, VIVA, and HALOGAS galaxies

Abstract: We present an analysis of morphological, kinematic and spectral asymmetries in observations of atomic neutral hydrogen (H i) gas from the Local Volume H i Survey (LVHIS), the VLA Imaging of Virgo in Atomic Gas (VIVA) survey and the Hydrogen Accretion in Local Galaxies Survey (HALOGAS). With the aim of investigating the impact of the local environment density and stellar mass on the measured H i asymmetries in future large H i surveys, we provide recommendations for the most meaningful measures of asymmetry for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 102 publications
(199 reference statements)
3
67
5
Order By: Relevance
“…Although this can be achieved in a variety of ways (e.g. Peterson & Shostak 1974;Tifft & Cocke 1988;Haynes et al 1998;Deg et al 2020;Reynolds et al 2020), we focus on statistics that capture asymmetry on different scales and then combine them, for convenience, into a single asymmetry measure. We apply the same procedures to our observed and simulated line profiles, whether or not the latter were modelled with instrumental noise.…”
Section: Quantifying the Asymmetries Of Unresolved H Line Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this can be achieved in a variety of ways (e.g. Peterson & Shostak 1974;Tifft & Cocke 1988;Haynes et al 1998;Deg et al 2020;Reynolds et al 2020), we focus on statistics that capture asymmetry on different scales and then combine them, for convenience, into a single asymmetry measure. We apply the same procedures to our observed and simulated line profiles, whether or not the latter were modelled with instrumental noise.…”
Section: Quantifying the Asymmetries Of Unresolved H Line Profilesmentioning
confidence: 99%
“…Compared to isolated central galaxies, satellite galaxies are more prone to tidal and ram-pressure stripping and, as a result, typically have H velocity profiles that are more asymmet-★ E-mail: aditya.manuwal@icrar.org ric (e.g. Reynolds et al 2020;Watts et al 2020a). Nevertheless, H surveys reveal a high incidence ( 50 per cent) of asymmetric line profiles among massive spiral galaxies (Richter & Sancisi 1994;Matthews et al 1998;Watts et al 2020a), even seemingly isolated ones (Haynes et al 1998;Espada et al 2011;Portas et al 2011); similar trends are also observed for dwarf galaxies (Swaters et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Of the ones that are relevant here, the most promising ones are minor tidal interactions, the accretion of gas from the intergalactic medium, an off-centre disc within its halo, and ram pressure stripping (Jog & Combes 2009). Reynolds et al (2020) find a trend of increasing asymmetry strength with density of the environment, as also indicated by Espada et al (2011). It is thus likely that ram pressure stripping and tidal interactions are the most likely scenarios in the higher density environments, with gas accretion explaining asymmetries seen in more isolated galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively isolated galaxies do sometimes exhibit morphological and kinematic asymmetries (e.g. Greisen et al 2009;Reynolds et al 2020), and the origin of this feature in UGC 9334 deserves further study that we reserve for future work.…”
Section: Ugc 8475 and Ugc 9334mentioning
confidence: 99%